Kenaf Fiber Composite in Automotive Industry: An Overview - F. Hassan; R. Zulkifli; M. J. Ghazali; Che Husna Binti Che Azhari (INSIGHT - Indonesian Society for Knowledge and Human Development, 2024)
Non-Indexed Publication